Is it worth using the coupled electrodialysis/electro-oxidation system for the removal of pesticides? Process modelling and role of the pollutant. (May 2020) - Raschitor, A.; Llanos, J.; Rodrigo, M.A.; Cañizares, P.
Abstract: This work presents the development of the electrodialysis/electro-oxidation (EDEO) technology, assessing the role of the pollutant and the modelling of the system in order to look for the key aspects for the development of the technology. According to the results obtained, it can be concluded that electrodialysis can be properly used to concentrate clopyralid, having the selected ionic exchange membranes (AMX) an adsorption capacity of 1.64 ± 0.26 mg cm −2 . Moreover, it was observed that BDD anodes exhibit a higher degradation and mineralization current efficiencies than MMO when using electro-oxidation (EO). The role of the supporting electrolyte was also assessed, observing a slight better performance of BDD with sulphate (maximum mineralization current efficiency of 80%) and a much superior degradation efficiency with chloride when selecting MMO as anode material. Regarding the EDEO technology, it was checked that this process only overcomes the performance of EO when using MMO anodes, a result that is explained by the ratio between degradation and transport rates. Finally, a simple model was presented and successfully used to predict the degradation rate constants and to simulate the performance of EDEO under different scenarios. These simulations confirm that the transport rate needs to overcome the degradation rate in order to assure a better performance of the EDEO system compared to the conventional EO. Moreover, the simulations explain the results obtained in the present and previous works revealing the key for a further development of the EDEO technology in the future. Graphical abstract: Image 1 Highlights: Clopyralid is efficiently concentrated by electrodialysis allowing the use of EDEO. AMX membranes has an adsorption capacity of clopyralid equal to 1.64 ± 0.26 mg cm −2 . BDD anode presents higher removal rates than MMO anode for clopyralid. A non-stationary CSTR model can be successfully used for modelling EO and EDEO. The key to achieve a more efficient process is to increase the transport rate.